Distribution and Abundance of the Onchidiidae of the Coastal Mangroves of Selangor, Peninsular Malaysia - A Sabri, N; R Singh, H (International Journal of Engineering and Technology, 2019)
The Onchidiidae family is ideal for studying the biodiversity of marine invertebrate species from sea to wetland environments. However, biodiversity studies of Onchidiidae species are rare. This study aimed to determine the distribution and abundance of the Onchidiidae from the coastal mangroves of the Selangor, west coast of Peninsular Malaysia by utilising the quadrat sampling method.Â A total of 647 specimens from six taxa (Family: Onchidiidae) were recorded from eight fringing coastal mangroves in Selangor coast. The most abundant taxa was Platevindex coriaceum (35.08%), followed by Peronina alta (28.13%), Platevindex luteum (16.85%), Platevindex sp. (14.68%), Onchidium tumidum (3.71%), and Onchidium typhae (1.55%). P. alta was most abundant within <10 m distance from the water body (18.75%), Platevindex sp. (5.86%) within 10 â€“ 20 m, P. coriaceum (10.16%) and O. typhae (1.76%) was highly distributed within 20 â€“ 30 m, while P. luteum was most concentrated within 40 â€“ 50 m from the water body. Onchidiidae was mostly abundant within <0.2 m from the mangrove floor where they were usually found on the mud, debris, mangrove tree roots and dead logs. The mean density for Onchidiidae at the fringing coastal mangroves in Selangor was 0.18 Â± 0.03 no/m2 and P. alta recorded the highest density (mean = 0.47 Â± 0.14 no/m2, total = 0.93 no/m2). The principal components analysis (PCA) showed that four geomorphological parameters (mud floor, debris floor, tree, and dead logs) and five physicochemical parameters (temperature, humidity, precipitation, salinity, and pH) determined the distribution of six Onchidiidae taxa in the Selangor coastal area.Â Â